Acting and advances of the pharmaceutical professional in the oncological scope (Research, Society and Development, 2021)
Introduction: The cancer patient requires several treatments, so the work aimed at this patient should be performed in a broad erway. The multiprofessional team is made up of doctors, nurses, nutritionists, psychologists, and the pharmacist, who is increasingly conquering his space. Objective: To know and discus sthrough a bibliographic survey the advance softhe pharmacist's performance in oncology. Methodology: This is a literature review through searches on LILACS, SciELO, MEDLINE, Science Direct and VHL platforms, articles and theses published from 2014 to 2019. Results and Discussion: The oncology pharmacist becomes the main instrument to obtain the proper quality of individualized pharmacotherapy. Regarding chemotherapy, the professional acts by selecting, acquiring, storing and standardizing the components that are paramount from the preparation to the dispensation of these antineoplastics. Even with all the support and attributions focused on the pharmaceutical profession, it is known that the totally satisfactory performance with pharmaceutical attention in oncologyis still a challenge. According to a survey of the profile of the pharmacist's performance in oncology conducted by Sobrafo in relation to the total hours dedicated to manipulation, it is true to say that 34.5% of these professionals reach 6 hours of manipulation and 15.6% reach 8 hours in this sector. Conclusion: Even with all the attributions and advances of the pharmaceutical professional, there are still some challenges related to the full exercise of pharmaceutical care, such as the excess of time in the handling sector, which makes other activities difficult.